2014
DOI: 10.1007/s10067-014-2568-4
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue thickness in patients with ankylosing spondylitis

Abstract: The purpose of our study was to measure epicardial adipose tissue (EAT) thickness as a novel indicator of atherosclerosis and cardiovascular risk factor in ankylosing spondylitis (AS) patients and to show the relationship with clinical parameters and inflammatory markers. Forty AS patients (42.75 ± 12.43 years) and 40 healthy individuals with no cardiovascular risk factor as the control group (43.02 ± 14.78 years) were included in the study. Carotid intima-media thickness (CIMT) and EAT thickness were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…Case-control studies allowing evaluation of carotid intima media thickness and endothelial dysfunction found a predisposition of FMF patients to atherosclerosis [4,5]. Mean platelet volume (MPV) and epicardial adipose tissue (EAT) thickness are novel parameters used in prediction of the risk of atherosclerosis [3,6-8]. Albeit contradictory results have been reported, there are some studies investigating the usefulness of MPV in assessment of atherosclerotic risk in cases with FMF [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Case-control studies allowing evaluation of carotid intima media thickness and endothelial dysfunction found a predisposition of FMF patients to atherosclerosis [4,5]. Mean platelet volume (MPV) and epicardial adipose tissue (EAT) thickness are novel parameters used in prediction of the risk of atherosclerosis [3,6-8]. Albeit contradictory results have been reported, there are some studies investigating the usefulness of MPV in assessment of atherosclerotic risk in cases with FMF [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…35 Nakanishi et al 36 used computed tomography to measure EFT levels and reported that patients with high levels had more coronary artery calcification. In studies by Cece et al 12 and Resorlu et al, 37 CIMT values in AS patients were found to be higher than those of the control group. In our study, AS patients had increased EFT thickness with high CIMT values.…”
Section: Discussionmentioning
confidence: 86%
“…The most common non-skeletal finding is acute anterior uveitis or iridocyclitis [10].The more rarely seen cardiac and pulmonary involvement affects mortality. In addition to increased carotid intima media thickness and epicardial fat tissue, ascending aortitis, aortic valve insufficiency and transmission defects may also be observed [11,12]. Airway disease, interstitial anomalies and pleural thickening occur in pulmonary involvement [13].…”
Section: Discussionmentioning
confidence: 99%